2018
DOI: 10.3171/2017.9.jns17176
|View full text |Cite
|
Sign up to set email alerts
|

The role of preoperative deep vein thrombosis screening in neurooncology

Abstract: OBJECTIVE Venous thromboembolism (VTE) is a major cause of morbidity in patients undergoing neurosurgical intervention. The authors postulate that the introduction of a routine preoperative deep vein thrombosis (DVT) screening protocol for patients undergoing neurosurgical intervention for brain tumors would result in a more effective diagnosis of DVT in this high-risk subgroup, and subsequent appropriate management of the condition would reduce pulmonary embolism (PE) rates and improve patient outcomes. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…VTE (venous thromboembolism) is the leading cause of morbidity in patients undergoing neurosurgical procedures, according to [ 19 ]. If a preoperative DVT screening protocol is implemented for patients having brain tumor surgery, the authors believe that this high-risk subgroup will be better identified as having DVT so that appropriate treatment can be given to minimize their risk of pulmonary embolism (PE) and improve their overall outcomes and quality of care.…”
Section: Related Workmentioning
confidence: 99%
“…VTE (venous thromboembolism) is the leading cause of morbidity in patients undergoing neurosurgical procedures, according to [ 19 ]. If a preoperative DVT screening protocol is implemented for patients having brain tumor surgery, the authors believe that this high-risk subgroup will be better identified as having DVT so that appropriate treatment can be given to minimize their risk of pulmonary embolism (PE) and improve their overall outcomes and quality of care.…”
Section: Related Workmentioning
confidence: 99%
“…11 Preoperative DVT screening protocol helps in reducing pulmonary embolism rates and improving patient outcomes in the neurosurgical population. 12 However, currently, there are no recommendations for preoperative DVT screening in this population. Our survey response depicts that most respondents are not considering preoperative DVT screening.…”
Section: Discussionmentioning
confidence: 98%
“…18 Incidence of moderate to severe anemia (hematocrit < 30%) in elective cranial surgery is around 2.7%. 12 Preoperative anemia in the neurosurgical population can be multifactorial and results in poor outcome, prolonged hospitalization, and excessive resource utilization. 19 20 It should be detected and corrected before elective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative strategy reported in the literature for patients who can safely tolerate delay of surgery might be considered for therapeutic anticoagulation. 26…”
Section: Early Detection and Prevention Of Vte Progressionmentioning
confidence: 99%